2015
DOI: 10.3892/mmr.2015.4274
|View full text |Cite
|
Sign up to set email alerts
|

Mangiferin attenuates contusive spinal cord injury in rats through the regulation of oxidative stress, inflammation and the Bcl-2 and Bax pathway

Abstract: Mangiferin has antioxidant, antiviral, apoptosis regulating, anti‑inflammatory, antitumor and antidiabetic effects, which can also inhibit osteoclast formation and bone resorption. However, whether mangiferin ameliorates the neurological pain of spinal cord injury (SCI) in ratS remains to be elucidated. The present study investigated the therapeutic effects of mangiferin on neurological function, the water content of spinal cord, oxidative stress, the expression of inflammatory cytokines and the protein expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 39 publications
1
35
0
Order By: Relevance
“…Interestingly, mangiferin ameliorates not only brain injury but also spinal cord injuries. In neurological pain due to contusive spinal cord injury in rats, mangiferin amended the water content of the spinal cord, the expression levels of inflammatory cytokines and apoptosis‐related proteins, thus attenuating contusive spinal cord injury in rats .…”
Section: Effect Of Mangiferin Against Inflammation Related Organ Dysfmentioning
confidence: 99%
“…Interestingly, mangiferin ameliorates not only brain injury but also spinal cord injuries. In neurological pain due to contusive spinal cord injury in rats, mangiferin amended the water content of the spinal cord, the expression levels of inflammatory cytokines and apoptosis‐related proteins, thus attenuating contusive spinal cord injury in rats .…”
Section: Effect Of Mangiferin Against Inflammation Related Organ Dysfmentioning
confidence: 99%
“…Furthermore, a report indicates that protocatechuic acid prevents osteoclast differentiation through regulating oxidative stress, inflammation and inducing apoptosis in RAW264.7 murine macrophage cells . In particular, avenanthramides (AVAs) with antioxidant properties increase osteoclast apoptosis and mangiferin can also inhibit osteoclast formation and bone resorption through regulating oxidative stress, inflammation and the Bcl‐2 and Bax pathway …”
Section: Discussionmentioning
confidence: 99%
“…37 In particular, avenanthramides (AVAs) with antioxidant properties increase osteoclast apoptosis 38 and mangiferin can also inhibit osteoclast formation and bone resorption through regulating oxidative stress, inflammation and the Bcl-2 and Bax pathway. 39 In addition, IL-15 stimulates apoptosis of osteoblasts via activation of NK cells by Caspase3. 40 Strikingly, in the report, we first proved that GLP2 exerts its effect in part through the upregulation of iNOS expression.…”
Section: Discussionmentioning
confidence: 99%
“…Both Bax and Bcl‐2 are quintessential genes in the Bcl‐2 family and represent apoptotic as well as anti‐apoptotic genes, respectively. The ratio of Bcl‐2 to Bax is considered a decisive factor and plays an important role in determining whether or not cells will undergo apoptosis (Mohammadi et al, ; Luo et al, ). Our results indicated that Bax positive cells gradually abated and was subsequently chaperoned by the upregulation of intensity in the anterior horn of the spinal cord in both Cur‐ and MP‐treated groups.…”
Section: Discussionmentioning
confidence: 99%